2017
DOI: 10.2341/16-211-l
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Bond Strength Between Resin Cement and Glass-Ceramic Using a Silane-Containing Universal Adhesive

Abstract: This study aimed to evaluate the effect of various silane-containing solutions on bonding between resin cement and glass ceramic after 24 hours and after six months of water storage. Glass-ceramic plaques (IPS e.max CAD) were sandblasted with aluminum oxide, etched with 10% hydrofluoric acid (HF), and divided into five "silane treatment" groups: RelyX Ceramic Primer (RCP), RelyX Ceramic Primer and Single Bond Plus (RCP+SB), Scotchbond Universal (SBU), Clearfil Ceramic Primer (CP), and no solution (HF-only cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 32 publications
0
25
0
4
Order By: Relevance
“…Seven different indirect substrates were considered in this review. These included lithium disilicate ceramic, 20,22,23,25,28‐39 yttrium‐stabilized zirconium dioxide ceramic, 20 ‐22, 24,27,32,37,40‐53 leucite‐reinforced ceramic, 20,54‐56 feldspathic porcelain, 32,59 polymer infiltrated ceramic material, 19,58 resin composite, 20,26,29,57,59‐66 and metal alloys 67–69 . The characteristics of these studies are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Seven different indirect substrates were considered in this review. These included lithium disilicate ceramic, 20,22,23,25,28‐39 yttrium‐stabilized zirconium dioxide ceramic, 20 ‐22, 24,27,32,37,40‐53 leucite‐reinforced ceramic, 20,54‐56 feldspathic porcelain, 32,59 polymer infiltrated ceramic material, 19,58 resin composite, 20,26,29,57,59‐66 and metal alloys 67–69 . The characteristics of these studies are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Keeping the orthodontic wire as close as possible to the adhesive interface is mandatory, but very small variations in distance can result in changes in stress distribution, which might contribute to cohesive failures in resin. Murillo‐Gómez et al (2017), have associated these type of failures with higher bond strength values.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 In this study, even though the majority of failures were adhesive, cohesive failures in resin composite and cohesive failures in the lithium disilicate substrate were detected. Other studies have also reported cohesive failures in lithium disilicate substrate, 23,24 however, if a failure is not purely cohesive in ceramic and occurs in more than one substrate, most studies classify it as a mixed failure, thus it is normally underreported. 25 Although pure adhesive failures demonstrate a better stress distribution during the test set-up, other studies have stated that micro-shear bond strength test can still present some of the disadvantages of the conventional "macro" shear bond strength test, such as nonuniform stress distribution concentrated in the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, so-called "universal" one-step self-etch adhesives have been developed, which can bond to various restorative materials, such as indirect resin composites, glass ceramics, zirconia, and noble and non-precious alloys, without any additional primer applications, as well as to enamel and dentin 7,8) , and are widely used for repairing resin composite restorations as well as for direct resin composite restoration as a photo-cure adhesive. In order to improve bonding to silica filler-containing resin composites and silica-based ceramics, these adhesives contain a silane coupling agent, which has two different functional groups that react with the methacrylate and the silica of the glass structure, respectively.…”
Section: Introductionmentioning
confidence: 99%